2021
DOI: 10.3389/fpls.2021.673337
|View full text |Cite
|
Sign up to set email alerts
|

LaPT2 Gene Encodes a Flavonoid Prenyltransferase in White Lupin

Abstract: Legume plants are rich in prenylated flavonoid compounds, which play an important role in plant defense and human health. In the present study, we identified a prenyltransferase (PT) gene, named LaPT2, in white lupin (Lupinus albus), which shows a high identity and close relationship with the other known PT genes involved in flavonoid prenylation in planta. The recombinant LaPT2 protein expressed in yeast cells exhibited a relatively strong activity toward several flavonols (e.g., kaempferol, quercetin, and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…To examine the products in the EpPT8 catalyzed reaction using kaempferol as substrate, their HPLC chromatographs, MS spectra and MS/MS spectra were acquired for the confirmation of chemical property. The above reaction products were shown at about 55% conversion ratio of substrate to product and possessed the same HPLC retention time and reference data as 8-prenylkaempferol standard ( Figure 4D , Figure S3 , S4 ) ( Liu et al., 2021b ), indicating that EpPT8 was able to prenylate kaempferol at C-8 position. To confirm the chemical structure, the EpPT8 catalyzed reaction products were further separated with preparative liquid chromatograph and determined by NMR experiments.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…To examine the products in the EpPT8 catalyzed reaction using kaempferol as substrate, their HPLC chromatographs, MS spectra and MS/MS spectra were acquired for the confirmation of chemical property. The above reaction products were shown at about 55% conversion ratio of substrate to product and possessed the same HPLC retention time and reference data as 8-prenylkaempferol standard ( Figure 4D , Figure S3 , S4 ) ( Liu et al., 2021b ), indicating that EpPT8 was able to prenylate kaempferol at C-8 position. To confirm the chemical structure, the EpPT8 catalyzed reaction products were further separated with preparative liquid chromatograph and determined by NMR experiments.…”
Section: Resultsmentioning
confidence: 72%
“…Recent study showed that the recombinant LaPT2 protein from Lupinus albus (Leguminosae) could also use kaempferol as substrate to produce 8-prenylkaempferol, and possessed activity towards a wide range of flavonoid substrates, including flavonols, flavones, and naringenin, but L. albus plants only accumulate a trace amount of 8-prenylkaempferol in roots ( Liu et al., 2021b ). In a more recent study, the recombinant EsPT2 protein from E. sagittatum was found to be able to prenylate both kaempferol and methylated kaempferol ( Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…2b; Table 1). Such in vivo and in vitro difference seems to be not occasional in prenyltransferase studies, since the functions of SfN8DT (Sasaki et al 2008) and LaPT2 (Liu et al 2021) were reported to be different between transgenic Arabidopsis thaliana and recombinant proteins. This phenomenon is probably caused by different microenvironments in vitro and in planta, including substrate concentration and accessibility, subcellular localization of enzymes, co-factors, competitive inhibition of enzyme activity, etc.…”
Section: Discussionmentioning
confidence: 98%
“…However, when GuILDT was expressed with isoliquiritigenin in tobacco in our study, no IBC accumulation was observed ( Figure 2B ; Table 1 ). Such in vivo and in vitro difference seems to be not occasional in prenyltransferase studies, since the functions of SfN8DT ( Sasaki et al., 2008 ) and LaPT2 ( Liu et al., 2021 ) were reported to be different between transgenic Arabidopsis thaliana and recombinant proteins. This phenomenon is probably caused by different microenvironments in vitro and in planta , including substrate concentration and accessibility, subcellular localization of enzymes, co-factors, competitive inhibition of enzyme activity, etc.…”
Section: Discussionmentioning
confidence: 98%